Pengaruh Kohesi dan Koherensi Pada Terbentuknya Wacana Yang Utuh - Gunasari, Ni Putu Candra Gunasari (Universitas Tabanan, 2025)
Discourse does not necessarily have to explicitly contain grammatical tools (conjunctions) to connect one idea with another, as logical relationships between parts of a discourse can be established without grammatical markers. The theories of cohesion and coherence are different; however, in practice, distinguishing between these two concepts can be quite challenging. A clause has a structure arranged according to specific sequence rules recognized by the speech community of a language. Discourse is a collection of sentences that form a unified and communicative piece of information. Research on discourse analysis has gained significant interest in recent times. It is therefore essential to take concrete steps, particularly in mastering language skills—especially writing—through continuous training. Two crucial elements for achieving writing proficiency are knowledge of writing and consistent practice, as writing is an integrated language skill aimed at producing a written text. In discourse, the presence of cohesion markers and coherence supporters is necessary.